The role of Artificial Intelligence (AI) in tests and assessment from the perspective of teachers in Jeddah education (The International Journal of Educational Sciences and Arts, 2025)
With AI's growing integration into various sectors, its potential to transform educational assessment practices is increasingly apparent. This research aims to examine how school teachers perceive the use of AI in creating, administering, and evaluating assessments, as well as its potential benefits and challenges. A quantitative-methods approach was employed, with 219 participants being surveyed. The results indicate that the perspectives of school teachers in Jeddah reveal a nuanced view of AI in educational assessments. The study also identifies several significant challenges that hinder the integration of AI in assessment in Jeddah’s educational sector. These challenges include a lack of training, financial and resource constraints, ethical concerns, resistance to change, and technical reliability issues. No significant differences were found in the perceptions of AI’s importance in assessment according to gender, school level, or experience. However, public-school teachers demonstrated significantly higher mean scores compared to private-school teachers, indicating a stronger belief in AI’s potential to enhance assessment practices.
Keywords: Artificial Intelligence (AI); Tests; Assessment; Teacher; Educational Assessment; Personalized Feedback; Automated Grading; Ethical Considerations